Mathematical Problem-Solving Ability from the Perspective of the Computational Thinking Approach - Dwi Fitdyawati, Shilviana; In'am, Akhsanul; Zukhrufurrohmah (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Computational thinking is a practical approach to solving mathematical problems that encourages students to think critically, creatively, and systematically. This type of research employs a descriptive, qualitative approach that aims to describe the mathematical problem-solving abilities of grade 9 students from private junior high schools in Malang, with a focus on computational thinking. The subjects of the study consisted of 6 students representing two high categories, two medium categories, and two low categories, based on the results of the mathematics exam. Data collection techniques include documents, such as student learning scores and tests to measure students' computational thinking abilities, as well as interviews to refine the test results. The data were then analysed based on computational thinking indicators, including decomposition, pattern recognition, generalisation, abstraction, and algorithmic thinking. In the final stage, a description of computational thinking-based problem-solving abilities is presented. The results showed that students in the high category met four of the five computational thinking indicators, except for the generalisation indicator. Students in the medium category met all indicators, while students in the low category only met two indicators: pattern recognition and abstraction. This study emphasises the importance of computational thinking in mathematics education, which aims to improve students' problem-solving skills. Further research may explore appropriate instructional models for the development of computational thinking. Abstrak Berpikir komputasional merupakan pendekatan praktis dalam memecahkan masalah matematika yang mendorong siswa untuk berpikir kritis, kreatif, dan sistematis. Jenis penelitian ini menggunakan pendekatan kualitatif deskriptif yang bertujuan untuk mendeskripsikan kemampuan pemecahan masalah matematika berbasis berpikir komputasional pada siswa kelas IX SMP Swasta di Malang. Subjek penelitian terdiri dari 6 siswa yang mewakili dua kategori tinggi, dua kategori sedang, dan dua kategori rendah, berdasarkan hasil ujian matematika. Teknik pengumpulan data meliputi dokumen, seperti nilai belajar siswa dan tes untuk mengukur kemampuan berpikir komputasional siswa, serta wawancara untuk menyempurnakan hasil tes. Data kemudian dianalisis berdasarkan indikator berpikir komputasional, meliputi dekomposisi, pengenalan pola, generalisasi, abstraksi, dan berpikir algoritmik. Pada tahap akhir, disajikan deskripsi kemampuan pemecahan masalah berbasis berpikir komputasional. Hasil penelitian menunjukkan bahwa siswa dalam kategori tinggi memenuhi empat dari lima indikator berpikir komputasional, kecuali indikator generalisasi. Siswa dalam kategori sedang memenuhi semua indikator, sedangkan siswa dalam kategori rendah hanya memenuhi dua indikator: pengenalan pola dan abstraksi. Studi ini menekankan pentingnya pemikiran komputasional dalam pendidikan matematika, yang bertujuan untuk meningkatkan keterampilan pemecahan masalah siswa. Penelitian lebih lanjut dapat menyelidiki model pembelajaran yang tepat untuk pengembangan pemikiran komputasional.